2018
DOI: 10.1002/jia2.25184
|View full text |Cite
|
Sign up to set email alerts
|

“My future is bright…I won't die with the cause of AIDS”: ten‐year patient ART outcomes and experiences in South Africa

Abstract: IntroductionSouth Africa is moving into a new era of HIV treatment with “treat all” policies where people may be on treatment for most of their lives. We need to understand treatment outcomes and facilitators of long‐term antiretroviral treatment (ART) adherence and retention‐in‐care in the South African context. In one of the first studies to investigate long‐term treatment outcomes in South Africa, we aimed to describe ten‐year patient outcomes at a large public‐sector HIV clinic in Johannesburg and explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Furthermore, the time pressure introduced by the SDI policy possibly resulted in the elimination and overall decline in the quality of psychosocial support offered to HIV positive clients [33‐35]. A qualitative study with HIV positive patients retained in HIV care for over ten years showed that the clinic environment, support networks and self‐efficacy for treatment adherence were critical facilitators of staying in care [33‐36]. In an observational cohort study, enrolling patients diagnosed with HIV under the SDI policy, we demonstrated that social preparation before HIV testing (disclosure of intention to test, partner/family support at the clinic on the day of HIV testing) were essential predictors of ART uptake, particularly among men [37].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the time pressure introduced by the SDI policy possibly resulted in the elimination and overall decline in the quality of psychosocial support offered to HIV positive clients [33‐35]. A qualitative study with HIV positive patients retained in HIV care for over ten years showed that the clinic environment, support networks and self‐efficacy for treatment adherence were critical facilitators of staying in care [33‐36]. In an observational cohort study, enrolling patients diagnosed with HIV under the SDI policy, we demonstrated that social preparation before HIV testing (disclosure of intention to test, partner/family support at the clinic on the day of HIV testing) were essential predictors of ART uptake, particularly among men [37].…”
Section: Discussionmentioning
confidence: 99%
“…At the interpersonal and social levels, stigma and lack of familial or peer support can be major factors, making access to care challenging [ 2 , 6 ]. The passive withdrawal or lack of typical familial and peer support structures can be detrimental and contribute towards disengagement [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antiretroviral therapy (ART) has changed the prognosis of AIDS, and has increased longevity and decreased mortality and morbidity [ 1 3 ]. The decision regarding the choice of antiretroviral regimen should consider factors such as: efficacy, immediate and long-term toxicity; the presence of co-infections and comorbidities; the concomitant use of other medicines; potential of adherence; adequacy to the patient's everyday routine; genetic barrier to drug resistance; medication and food interactions and the cost of medication [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%